A COGNITIVIST AND CLASSICAL SYNERGY FOR ENVIRONMENTAL EDUCATION (CIPEEX, 2026)
This study examines how integrating a cognitivist approach with classical educational principles can promote meaningful learning and critical thinking in addressing contemporary environmental and sustainability challenges. It begins with the premise that current educational models often fail to equip students with the necessary competencies to understand environmental complexity. Drawing on the revival of the Liberal Arts—particularly the Trivium—in dialogue with David Ausubel's theory of meaningful learning, the research explores its potential to enrich pedagogical practices and enhance understanding of how people mathematically apprehend environmental reality. Grounded in cognitivist and classical educational frameworks, as well as the principles of critical environmental education, the theoretical and pedagogical integration of cognitivism, the educational tradition, and sustainability is expected to strengthen environmental awareness and contribute to the development of reflective, ethical, and critical individuals.
Keywords: meaningful learning; environmental education; SDG 4.7.